Hydrocarbon leakage driven by Quaternary glaciations in the Barents Sea based on 2D basin and petroleum system modeling. (April 2022) - Kishankov, Aleksei; Serov, Pavel; Bünz, Stefan; Patton, Henry; Hubbard, Alun; Mattingsdal, Rune; Vadakkepuliyambatta, Sunil; Andreassen, Karin
Abstract: The Barents Sea has experienced intense erosion throughout the Cenozoic due to uplift and repeated episodes of glaciation. This, in turn, has driven large pressure and temperature fluctuations in the sediment substrate along with rearrangement of thermogenic oil and gas accumulations. As a result, some hydrocarbon fields have relatively shallow depths, and natural gas release is widespread. This study focuses on the process of hydrocarbon leakage from the Realgrunnen reservoir - encompassing the Hanssen and Wisting discoveries - to the shallow subsurface caused by repeated cycles of glacial erosion in the central Barents Sea throughout the Quaternary. We apply 2D basin and petroleum system modeling to two seismic sections using data from two wells and run ten different scenarios that test model sensitivity to key parameters. We find that the primary factors governing gas leakage are the erosion amount, its distribution between glacial and preglacial stages, and the timing of the glaciations. Our results demonstrate that intense oil and gas leakage from the Realgrunnen reservoir occurs primarily through widespread faults activated during the first deglaciation episode. Further considerable gas leakage occurs by the seal breach after a critical overburden thickness is eroded and pressure on the reservoir decreases to ca. 9 MPa. Modeling reveals that the first deglaciation episode causes up to ca. 20% loss of oil and gas from the reservoir, whereas leakage after the seal breach yields a further ca. 15% decrease in gas. Our results are supported by seismic analyses that demonstrate hydrocarbon leakage in the study area. Highlights: Most intensive hydrocarbon leakage occurred through open faults during the first Quaternary deglaciation episode. Gas is also subject to intense capillary leakage through overburden rocks eroded below a critical thickness. Gas leakage is dependent on the glacial and preglacial erosion thicknesses and the glacial history.